The Argentine Black and White Tegu in South Florida: Population Growth, Spread, and Containment - Rebecca G. Harvey; Frank J. Mazzotti (EDIS, 2016)
Florida is home to more nonnative species of reptiles and amphibians than anywhere else in the world because of its subtropical climate, large areas of disturbed habitats, and thriving trade in exotic pets. Although pythons have received the majority of public attention, invasive lizards also pose a significant threat to south Florida’s native wildlife and ecosystems, and a good example is the Argentine black and white tegu. Learn more about this exotic lizard in this 3-page fact sheet written by Rebecca G. Harvey and Frank J. Mazzotti, and published by the Wildlife Ecology and Conservation Department, November 2015.